Sensory Characteristics of Semprit Cookies with Variations in Mocaf Flour and Kepok Banana Flour Formulations - Tamara, Alberta; Sari, Fitri Komala; Pangesthi, Lucia Tri; Muyasyaroh, Hidayatun (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Semprit cookies are traditional Indonesian baked products characterized by their crisp texture, distinctive shape, and balanced flavor. This study aimed to evaluate the sensory characteristics of semprit cookies formulated with varying proportions of mocaf flour (Modified Cassava Flour) and kepok banana flour as local ingredient alternatives to wheat flour. Six formulations (F1-F6) were prepared with mocaf:banana flour ratios ranging from 100:0, 80:20, 60:40, 40:60, 20:80, 0:100 using a randomized complete design. Hedonic tests were conducted with 30 semi-trained panelists to assess color, aroma, taste, texture, and overall acceptability. ANOVA results indicated significant differences (p < 0.05) in color, taste, texture, and overall attributes, while aroma showed no significant variation (p = 0.683). The highest color preference was observed in F2 (80:20 mocaf:banana), whereas taste, texture, and overall acceptability were most favored in F4 (40:60 mocaf:banana). Conversely, F6 (0:100 banana flour) consistently received the lowest scores in taste and overall preference. These findings suggest that partial substitution of mocaf with kepok banana flour enhances sensory quality, particularly in taste and texture, while maintaining consumer acceptance. The optimal formulation identified was F4, which achieved superior ratings in taste, texture, and overall preference, supporting the potential of local flour diversification to improve product quality and reduce dependence on imported wheat flour. This study provides a scientifically-grounded optimal formulation for gluten free semprit cookies, offering a practical model for a product development using local resources to enhance food sovereignty.